Implementation of Webservice Security: A Case Study on HTTPS Usage and ARP Spoofing Attack Threats - Fitri, Novi Aryani; Maulana, Okta (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
This study explores network security within a simulated environment built using VirtualBox, focusing on comparing the HTTP and HTTPS protocols in protecting data from eavesdropping. The research follows the PPDIOO model (Prepare, Plan, Design, Implement, Operate, and Optimize), including system requirements mapping and the setup of a virtual network environment that supports VLAN and data security. Two main scenarios were tested: an authorized user securely accesses a server using HTTPS, and another where an attacker attempts to intercept communication between the client and server using HTTP. The results indicate that HTTPS effectively protects data from eavesdropping attempts by attackers, while HTTP leaves security vulnerabilities that can be exploited to steal sensitive information. This study underscores the importance of using secure protocols like HTTPS in VLAN-based networks to protect data from eavesdropping and other threats. Additionally, the research paves the way for developing further security measures in network management, such as firewalls, intrusion detection systems (IDS), and more advanced encryption.